2019
DOI: 10.1016/j.cell.2019.02.036
|View full text |Cite
|
Sign up to set email alerts
|

Steroid Hormone Function Controls Non-competitive Plasmodium Development in Anopheles

Abstract: Graphical AbstractHighlights d Human malaria parasites interact non-competitively with their mosquito vectors d Mosquito hormone signaling co-regulates egg and parasite development d Parasites use host lipids for their growth via a mosquito lipid transporter d Parasites respond to mosquito metabolism with consequences for vector controlThe development of the malaria-causing parasite Plasmodium falciparum depends on its ability to exploit the sexual cycle of its mosquito host in a noncompetitive manner. SUMMARY… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
203
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(248 citation statements)
references
References 78 publications
24
203
5
Order By: Relevance
“…While an additional feeding does not limit human malaria parasite numbers unlike their rodent malaria counterparts (Figures 1 and 3), when evaluating oocyst numbers we noticed stark differences in parasite growth between Plasmodium species in the surviving oocysts (Figure 4). P. falciparum oocysts are significantly larger when mosquitoes receive an additional blood- or protein-meal when compared to mosquitoes maintained on sucrose alone after the infectious bloodmeal (Figure 4A), arguing that human malaria parasites are able to utilize host resources to accelerate their growth as previously suggested (Costa et al, 2018; Werling et al, 2019). Differences in oocyst size between blood- or protein-meal were not significant (Figure 4A).…”
Section: Resultssupporting
confidence: 64%
See 1 more Smart Citation
“…While an additional feeding does not limit human malaria parasite numbers unlike their rodent malaria counterparts (Figures 1 and 3), when evaluating oocyst numbers we noticed stark differences in parasite growth between Plasmodium species in the surviving oocysts (Figure 4). P. falciparum oocysts are significantly larger when mosquitoes receive an additional blood- or protein-meal when compared to mosquitoes maintained on sucrose alone after the infectious bloodmeal (Figure 4A), arguing that human malaria parasites are able to utilize host resources to accelerate their growth as previously suggested (Costa et al, 2018; Werling et al, 2019). Differences in oocyst size between blood- or protein-meal were not significant (Figure 4A).…”
Section: Resultssupporting
confidence: 64%
“…While no differences in P. berghei oocyst size were detected, P. falciparum oocysts significantly increased following additional feeding, suggesting that human malaria parasites utilize the added resources provided in a blood- or protein-meal to increase their growth. Previous work argues that the increase in lipid resources that accompany feeding are utilized by the developing oocyst for growth and sporozoite production (Costa et al, 2018; Werling et al, 2019). Moreover, an additional feeding increases the number of P. falciparum salivary gland sporozoites (Ponnudurai et al, 1989; Rosenberg and Rungsiwongse, 1991), arguing that this increased growth may enhance the potential for malaria transmission.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, given the importance of the JNK pathway in the An. gambiae immune response to some Plasmodium infections (Garver et al, 2013; Ramphul et al, 2015) and the centrality of 20E to mosquito physiology and parasite development (Werling et al, 2019), it will be informative to examine whether 20E signaling in other contexts (e.g. after blood feeding) also engages with the JNK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Vg expression decreased significantly in mosquitoes exposed to trypanosomes but was not modified by another eukaryotic microorganism, such as P. yoelii, when it was ingested alone ( Fig 3A). To strengthen this finding, we also tested the expression of another lipid transporter, the Lipophorin (Lp), another yolk protein precursor in mosquitoes [45,46], and also controlled via the 20E pathway [44]. We observed that, as for Vg expression, Lp expression is decreased 48h post trypanosome ingestion (S2A Fig).…”
Section: Trypanosoma Ingestion Affects the Reproductive Fitness In Amentioning
confidence: 86%
“…Mosquito egg maturation induces the expression of the gene encoding for the precursor of the major yolk protein, vitellogenin (Vg) through the activation of the 20-hydroxyecdysone (20E) pathway [42][43][44]. In order to measure the effect of trypanosome ingestion on mosquito reproductive fitness, we measured expression of Vg 48h after feeding on blood with or without trypanosomes.…”
Section: Trypanosoma Ingestion Affects the Reproductive Fitness In Amentioning
confidence: 99%